Menghadirkan Khotbah yang Berdaya Tarik bagi Generasi Z: Studi Kasus pada Gereja Pemberita Injil di Jakarta - Halim, Stevan (Sekolah Tinggi Teologi Simpson Ungaran, 2024)
This article reveals the characteristics of Generation Z as a sermon listener, specifically those found within Generation Z at Gereja Pemberita Injil in Jakarta, based on their experiences of listening to sermons. The research method used in this study is a qualitative research method with an ethnographic approach. This approach allows the researcher to dissect and study the worldview and interactions of Generation Z when listening to sermons. The main goal of this study is to identify the characteristics of Generation Z as sermon listeners, thereby developing appropriate strategies for delivering sermons to Generation Z at Gereja Pemberita Injil in Jakarta. Based on the result of the research, there are four characteristics of Generation Z as listeners to sermon: Generation Z wants to be connected in preaching; Generation Z listens sermon using their imagination; Generation Z listens sermon with their faith; Generation Z views the preacher as an authorized person, yet approachable figure. Based on these characteristics, there are some of the proposed strategies to preaching to Generation Z at Gereja Pemberita Injil: preaching with conviction; preaching by involving the daily life; preaching using story; and preaching by offering challenges.